Africa's Pulse, October 2013 : An Analysis of Issues Shaping Africa's Economic Future - World Bank (Washington, DC, 2014)
This Africa's pulse newsletter includes the following headings: economic prospects for Sub-Saharan Africa remain strong, but growth is vulnerable to a sharp decline in commodity prices; the region's progress on reducing poverty has been slow, hindered by high inequality; and faster reduction in poverty will require growth with equity.